2021
DOI: 10.1073/pnas.2100561118
|View full text |Cite
|
Sign up to set email alerts
|

DNAse-dependent, NET-independent pathway of thrombus formation in vivo

Abstract: The contribution of NETs (neutrophil extracellular traps) to thrombus formation has been intensively documented in both arterial and venous thrombosis in mice. We previously demonstrated that adenosine triphosphate (ATP)–activated neutrophils play a key role in initiating the tissue factor–dependent activation of the coagulation cascade, leading to thrombus formation following laser-induced injury. Here, we investigated the contribution of NETs to thrombus formation in a laser-induced injury model. In vivo, tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 31 publications
(36 reference statements)
0
48
0
1
Order By: Relevance
“…The authors also showed the importance of adenosine triphosphate (ATP), which plays an indispensable role in the recruitment and activation of neutrophils in the vascular endothelium, and the activated endothelium is a potential physiological source of ATP [2]. Finally, in 2021, our team demonstrated the involvement of NETs in this laser thrombosis model [24]. Indeed, intravital microscopy experiments showed that the injection of DNAse I (Figure 4), as well as the injection of apyrase, a known ATPase, into the general circulation of WT mice induced a strong decrease in the size of the thrombus after laser beam injury, thus suggesting a possible involvement of NETs in this model.…”
Section: The Ablative Laser Thrombosis Modelmentioning
confidence: 89%
See 3 more Smart Citations
“…The authors also showed the importance of adenosine triphosphate (ATP), which plays an indispensable role in the recruitment and activation of neutrophils in the vascular endothelium, and the activated endothelium is a potential physiological source of ATP [2]. Finally, in 2021, our team demonstrated the involvement of NETs in this laser thrombosis model [24]. Indeed, intravital microscopy experiments showed that the injection of DNAse I (Figure 4), as well as the injection of apyrase, a known ATPase, into the general circulation of WT mice induced a strong decrease in the size of the thrombus after laser beam injury, thus suggesting a possible involvement of NETs in this model.…”
Section: The Ablative Laser Thrombosis Modelmentioning
confidence: 89%
“…Morphologically, electron microscopy experiments in particular allow the characterization of neutrophils entering in NETosis with disrupted nuclear and plasma membranes, a clear cytoplasm with granules approaching the center of the cell close to the nucleus and finally extracellular DNA fibers [24].…”
Section: Neutrophils Extracellular Traps (Nets)mentioning
confidence: 99%
See 2 more Smart Citations
“…Li et al noted a decrease in inflammatory cytokines paired with attenuation of platelet activation and thrombus formation following NET degradation with the inhibitor DNAse [168]. In another study, DNAse lessened ATP and ADP-induced thrombus formation in vivo, although it did not affect NET formation [169]. The DNAse inhibitor dornase alfa has recently gained attention towards COVID-19 treatment, with improvement in patient oxygenation being noted following its use in vitro and in vivo [170][171][172], while it remains to be explored whether these agents can influence clinical outcomes by halting platelet activation among other pathways.…”
Section: Therapeutic Implicationsmentioning
confidence: 96%